Drought response of five conifer species under contrasting water availability suggests high vulnerability of Norway spruce and European larch. (10th August 2013) - Lévesque, Mathieu; Saurer, Matthias; Siegwolf, Rolf; Eilmann, Britta; Brang, Peter; Bugmann, Harald; Rigling, Andreas
Abstract The ability of tree species to cope with anticipated decrease in water availability is still poorly understood. We evaluated the potential of Norway spruce, Scots pine, European larch, black pine, and Douglas‐fir to withstand drought in a drier future climate by analyzing their past growth and physiological responses at a xeric and a mesic site in Central Europe using dendroecological methods. Earlywood, latewood, and total ring width, as well as the δ13C and δ18O in early‐ and latewood were measured and statistically related to a multiscalar soil water deficit index from 1961 to 2009. At the xeric site, δ13C values of all species were strongly linked to water deficits that lasted longer than 11 months, indicating a long‐term cumulative effect on the carbon pool. Trees at the xeric site were particularly sensitive to soil water recharge in the preceding autumn and early spring. The native species European larch and Norway spruce, growing close to their dry distribution limit at the xeric site, were found to be the most vulnerable species to soil water deficits. At the mesic site, summer water availability was critical for all species, whereas water availability prior to the growing season was less important. Trees at the mesic were more vulnerable to water deficits of shorter duration than the xeric site. We conclude that if summers become drier, trees growing on mesic sites will undergo significant growth reductions, whereas at their dry distribution limit in the Alps, tree growth of the highly sensitive spruce and larch may collapse, likely inducing dieback and compromising the provision of ecosystem services. However, the magnitude of these changes will be mediated strongly by soil water recharge in winter and thus water availability at the beginning of the growing season.